Mortality and Air Pollution Effects of Air Quality Interventions in Delhi and Beijing - Jayati Sinha; Naresh Kumar (Frontiers in Environmental Science, 2019)
Ambient air pollution alone accounts for more than 3 million premature deaths worldwide. Low and Middle Income Countries (LMIC) account for most (~87%) of this disease burden. Air pollution in the megacities of these countries has risen to the levels of public health hazards forcing the cities to take emergency measures, such as issuing red alerts and vehicle-rationing interventions (VRI). Using in-situ and high-resolution satellite data, this research examines the efficacy of VRI in Delhi and Beijing, two of the most polluted cities of LMIC. This research shows that VRI reduced particulate matter (PM) ≤ 2.5 μm in aerodynamic diameter (PM2.5) in Beijing during the 2008 Summer Olympics. However, such interventions implemented in 2015 and 2016 in Beijing and in 2016 in Delhi were ineffective in improving air quality. Moreover, the effects of such interventions were short lived, for example 54% of the cleaning in Beijing disappeared within 2 weeks after the Olympics, and Delhi witnessed a 34% increase in PM2.5 during the 2 weeks after the interventions. Both cities observed excess cardiopulmonary mortality even during the interventions. Short- and long-term preventive and mitigation strategies are needed to manage the air pollution disease burden.